The role of secure base and safe haven: a means of re-constructing the broken-self in Yvonne Vera's Under the Tongue - Dodhy, Shamaila; Jujar Singh, Hardev Kaur; Wan Yahya, Wan Roselezam; Bahar, Ida Baizura (Universiti Putra Malaysia Press, 2017)
Yvonne Vera is certainly the most successful and imaginative female novelist to emerge from Zimbabwe and conceivably one of the most significant writers of Africa. Her prose is valued for its characteristic lyricism and its lightness of touch which paradoxically highlight silenced and weighty realities of life. Being a Zimbabwean, she has directly experienced generational trauma of colonial oppression, horrors of guerrilla war and brutal killings of civilians in post-independence era. In 1990s, researchers have worked on trauma studies focusing on the sufferings of Whites like in the Holocaust and war veterans of Vietnam but less attention has been paid to the sufferings of black women. This study endeavours to locate Vera's texts within the theoretical debates of trauma studies. I intend to focus on Yvonne Vera's Under the Tongue (1996) which is about a sexual assault of a pre-adolescent girl by her own father, written against the backdrop of severe guerrilla warfare against colonialism. It aims to analyse the recovery of the protagonist in light of John Bowlby's Attachment Theory. This research will strive to study the role of secure base and safe haven which function as a mean of re-constructing the broken-self of the protagonist. In certain cases, nature or religion helps the healing process of the individual but the paper will establish how affectionate attachment figures have comforting, healing and therapeutic effects on the suffering individual. This will in turn help to reconstruct the broken-self and enable the survivor to face the society with confidence.